Mesenchymal stem cell-based therapies for treating well-studied neurological disorders: a systematic review - Patel, Gaurav Deepak; Liu, Lichao; Li, Ailian; Yang, Yun-Hsuan; Shen, Chia-Chi; Brand-Saberi, Beate; Yang, Xuesong (Frontiers in Medicine, 2024)
Background Millions of people across the globe are affected by conditions like Amyotrophic Lateral Sclerosis (ALS), Parkinson’s Disease (PD), Multiple Sclerosis (MS), Spinal Cord Injury (SCI), and Traumatic Brain Injury (TBI), although most occurrences are common in the elderly population. This systematic review aims to highlight the safety of the procedures, their tolerability, and efficacy of the available therapies conducted over the years using mesenchymal stem cells (MSCs) in treating the neurological conditions mentioned above. Methods PubMed was used to search for published data from clinical trials performed using mesenchymal stem cells. Studies that provided the necessary information that mentioned the efficacy and adverse effects of the treatment in patients were considered for this review. Results In total, 43 manuscripts were selected after a strategic search, and these studies have been included in this systematic review. Most included studies reported the safety of the procedures used and the treatment’s good tolerability, with mild adverse events such as fever, headache, mild pain at the injection site, or nausea being common. A few studies also reported death of some patients, attributed to the progression of the disease to severe stages before the treatment. Other severe events, such as respiratory or urinary infections reported in some studies, were not related to the treatment. Different parameters were used to evaluate the efficacy of the treatment based on the clinical condition of the patient. Conclusion Mesenchymal stem cells transplantation has so far proven to be safe and tolerable in select studies and patient types. This systematic review includes the results from the 43 selected studies in terms of safety and tolerability of the procedures, and several adverse events and therapeutic benefits during the follow-up period after administration of MSCs.